1995
DOI: 10.12693/aphyspola.88.759
|View full text |Cite
|
Sign up to set email alerts
|

New Local Vibrational Modes Related to Silicon in Bulk AlGaAs

Abstract: A silicon-related local vibrational mode absorption in AlGaAs is reported for the first time. It consists of six peaks grouped around 450 cm -1 which form a distinct pattern. We believe tlat the new local vibrational mode absorption is a fingerprint of a single defect. Among the discussed microscopic structures the most plausible is a SiG a -SiA S pair complex with Silks acceptor interacting with different Ga, Al nearest neighbour local environments.PACS numbers: 61.72. Vv, 63.20.Pw, 71.55.Eq A cucial facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
3
1
0
Order By: Relevance
“…The absorption cannot be due to a transition to either the valence band or the nearest conduction band for energetical reasons. It is thought that it is a transition to the X 3 -band minimum, in agreement with Kaczor et al (1993) and our previous results on Si. Note, that a very similar MCDA has been observed previously for shallow Te 0 and S 0 donors in GaP, which was interpreted as a transition to the L-band minimum (Spaeth et al 1993) (see figure 7(b) for comparison).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The absorption cannot be due to a transition to either the valence band or the nearest conduction band for energetical reasons. It is thought that it is a transition to the X 3 -band minimum, in agreement with Kaczor et al (1993) and our previous results on Si. Note, that a very similar MCDA has been observed previously for shallow Te 0 and S 0 donors in GaP, which was interpreted as a transition to the L-band minimum (Spaeth et al 1993) (see figure 7(b) for comparison).…”
Section: Discussionsupporting
confidence: 92%
“…The failure to see the MCDA in an LPE sample with x = 0.35 (Peale et al 1991) seems consistent with the failure to see the IR band above 0.5 eV for x = 0.37 reported by Mori et al (1992). However, Kaczor et al (1993) reported an IR band peaking at 0.53 eV for x = 0.3 in a sample also grown by the LPE method, but apparently from a different crystal grower. It is not clear why this IR band was not observed either by Peake et al (1991) or by Mori et al (1992) for a similar Al content.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations